A Comparison of the Spiritual Participation of On-Campus and Theological Distance Education Students. Issue 2 (November 2015) - Nichols, Mark
Abstract : Distance education has a well-established heritage as an effective means of formal higher learning. Despite this, its role in theological education is actively resisted by many evangelical Christian theorists. The main reason for this reluctance to endorse theological distance education is the concern that distance students do not have an adequate formation experience as they learn. Formation is a term representative of development as a Christian disciple, typically measured in terms of spiritual maturity. This study compares the spirituality characteristics of on-campus and distance students studying the same undergraduate degree programme at Laidlaw College, a theological education provider in New Zealand. The Christian Spiritual Participation Profile (CSPP) instrument was applied. Findings indicate no significant difference across all measures, including those related to the propensity for further spiritual growth. Significant differences were found between full-time and part-time students, the latter experiencing better overall formational development.